POLITICAL INTERESTS AND POLITICAL DECISIONS: THE POSSIBILITIES OF FORMING A DEMOCRATIC AGENDA - KHMELNIKOV, Yehor (Fìlosofìâ ta polìtologìâ v kontekstì sučasnoï kulʹturi, 2024)
The article is devoted to the study of political interest as a hidden determinant of the activity of associated and non-associated pressure groups (informal lobbying) within the bureaucratic power vertical. Applying modern interdisciplinary methodological tools, the author offers a rationale for the expediency of public articulation of political interests, elimination of hidden lobbying, as well as non-public agreements between the main political players, which slow down the modernization of the institutional environment of the democratic political system. The article reveals and describes the optimal efforts of the Ukrainian political class, which will be aimed at implementing the specified strategic changes. The author reveals an explanation of the functioning of the mechanisms by which interest groups operate and their influence on the formation of the agenda. The crucial importance of interest groups for understanding the dynamics of political decision-making is noted. It is emphasized that group actors are working to bring their issues to the top of the political agenda. The text examines the functionality of providing well-grounded and reasoned information by interested groups that reinforces the importance of their demands. The paper addresses demonstrations, petitions, and social media campaigns as common tactics used to mobilize public opinion and pressure political institutions into action. The article analyzes the pooling of resources and efforts by associated interest groups that purposefully increase the likelihood that their issues will be high on the political agenda. It is noted that publicizing demands and problems can lead to a change in the course and strategy of the current leadership or power team. It has been established that by consistently advocating their cause in public, group actors can ensure consideration of agenda items by politicians and attract media attention. Attention is paid to the cooperation of political forces and interested groups to obtain detailed information and recommendations during the development of draft laws or regulatory acts. Emphasis is placed on the priorities of elected officials who seek to conform to the “mainstream” of public opinion and public sentiment. In the final part of the article, the author emphasizes that the full representation of political interests and the interests of minority groups that are not in the mainstream of public attention. It was concluded that the institutional structure of European democracy is more open to the development of public interests. Therefore, for modern Ukraine, an important element is the formation of structures of political arbitration regarding the conflict of political interests or the provision of this functionality to already existing institutions